APOE ε4, Alzheimer’s disease pathology, cerebrovascular disease, and cognitive change over the years prior to death - Yu, Lei (2013)
BACKGROUND: Much remains to be learned about the effect of the APOE ε4 allele on the trajectory of cognitive aging including the onset of terminal decline and rates of decline before and after, particularly in the presence of Alzheimer’s disease (AD) brain pathology. OBJECTIVE: To examine the association of APOE ε4 allele with the late-life cognitive trajectory and test the hypothesis that association of ε4 with cognitive decline is explained by AD neuropathology. METHODS: Participants (N=581) came from two longitudinal clinical-pathologic studies of aging and dementia, the Religious Orders Study and the Memory and Aging Project, which involve uniform annual cognitive assessments and brain autopsy. Longitudinal measures of cognition were derived from detailed annual neuropsychological testing. Participants with 1 or more copies of ε4 allele (ε2/4 excluded) were considered ε4 carriers. Global AD pathology was summarized based on counts of neuritic plaques, diffuse plaques and neurofibrillary tangles. Separate measures of amyloid load and tangle density were assessed using immunohistochemistry. A uniform examination was conducted to document chronic cerebral infarctions. Lewy bodies were identified using alpha-synuclein immunostained sections of substantia nigra, limbic, and neocortical regions. Random change point models were applied to examine the association of ε4 allele with onset of terminal decline as well as pre-terminal and terminal slopes. RESULTS: On average, the onset of terminal decline occurred around 3 years before death and the rate of terminal decline was 8-fold faster than the pre-terminal decline. The presence of ε4 allele was associated with an earlier onset of terminal decline and faster rates of decline before and after the onset. After adjusting for global AD pathology, the ε4 allele was no longer associated with onset of terminal decline or pre-terminal slope, and the association with terminal slope became marginal. Similarly, ε4 allele was not associated with trajectory of cognitive aging after replacing global AD pathology with the more molecularly-specific measures of amyloid and tau tangles. The result was essentially unchanged after controlling for other common age-related brain pathologies. CONCLUSION: The APOE ε4 allele is an important determinant of the change in late-life cognition, including terminal decline. The association is primarily working through AD pathology.